Medellín, a city transformed by its management. Analysis of the management of its Historical Center (1990- 2015) - Núñez Coronel, Débora (2019)
The investigation seeks to carry out an analysis of the management of Colombian historical centers, relevant due to the efficacy of their current management. It has as its main character the city of Medellin, on which interventions have been carried out specifically during the last 25 years, from 1990 to 2015. The analysis is framed within the general context of heritage within Colombia, and includes the examination of some official government documents, and some analysis of the political and patrimonial approaches on which the strategies undertaken by the state are based on. All of these documents, used to create the local policies of Medellín, were reviewed, in order to be able to know the employed strategies in depth. It was also necessary to review the local Plan of Territorial Organization (POT), which pursues heritage conservation and city development, and is articulated in the Municipal Development Plan (PDM), both of which are part of the government’s strategy for the comprehensive improvement of neighborhoods.